ANALYSIS OF TRANSFORMATIONAL LEADERSHIP IN THE IMPLEMENTATION OF EMPLOYEE DISCIPLINE IN BAPPELITBANGDA, WAJO DISTRICT - Asmanurhidayani; Saniyyah Putri Salsabila Said; Syamsiar; Nurcaya (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Leadership can be considered successful if it can direct all subordinates without any protest. Therefore, the role of a leader is crucial in an organization. It's not just one or two individuals with similar personalities; rather, many subordinates within an office possess varying characteristics, making it challenging for a leader to ensure compliance with policies and decisions. The research question addressed is how and what are the barriers and enablers of transformational leadership in the implementation of employee discipline at the Wajo Regency Research and Development Agency (Bappelitbangda). The purpose of this study is to analyze and identify transformational leadership in the implementation of employee discipline at the Wajo Regency Research and Development Agency (Bappelitbangda). This study employed a qualitative descriptive method. Data collection techniques included observation, interviews, and documentation. Data analysis utilized triangulation. Based on the research findings, transformational leadership in the implementation of employee discipline at the Wajo Regency Research and Development Agency (Bappelitbangda) revealed a leadership model that is more inspiring to coworkers, progressive, open-minded, provides a good example, and motivates employees to be more disciplined in their work, effectively and efficiently, thereby achieving predetermined goals